2021
DOI: 10.1088/1674-1137/abe112
|View full text |Cite
|
Sign up to set email alerts
|

An improved semi-empirical relationship for cluster radioactivity *

Abstract: An improved semi-empirical relationship for cluster radioactivity half-lives is proposed by introducing an accurate charge radius formula and an analytic expression of the preformation probability. Moreover, the cluster radioactivity half-lives for the daughter nuclei around 208Pb or its neighbors and the 12C radioactivity half-life of 114Ba are calculated within the improved semi-empirical relationship. It is shown that the accuracy of the new relationship is improved significantly compared to its predecessor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…In addition, a recent study reported that cluster radioactivity half-lives increase as the size of the emitted cluster increases [32,38]. Therefore, the mass number ( ) and charge number ( ) of the emitted cluster are crucial factors in the investigation of cluster radioactivity half-lives.…”
Section: C=1592;mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study reported that cluster radioactivity half-lives increase as the size of the emitted cluster increases [32,38]. Therefore, the mass number ( ) and charge number ( ) of the emitted cluster are crucial factors in the investigation of cluster radioactivity half-lives.…”
Section: C=1592;mentioning
confidence: 99%
“…Moreover, with the development of α decay and cluster radioactivity exploration, intensive phenomenological semi-empirical relationships based on the above theoretical approaches and/or models, as generalizations of the striking law of half-lives in logarithmic form and the decay energy in the case of α decay proposed by Geiger and Nuttall [28,29], have been effectively applied to the investigation of cluster radioactivity [30][31][32][33][34] because they both share the quantum tunneling mechanism. For instance, in 2004, Ren et al extended the famous Viola-Seaborg formula from α decay [35,36] to complex cluster radioactivity (EVS) [37].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the cluster preformation probability is key to calculating cluster radioactivity half-lives. In 1988, Blendowske and Walliser [58] found that is related to the α preformation probability via…”
Section: Q Cmentioning
confidence: 99%
“…(PCM) [26], the modified generalized liquid drop model (MGLDM) [18,27], the Coulomb and proximity potential model (CPPM) [28], and the double-folding potential model [30]. In previous studies, the value, as a crucial input, is adopted from the measurements in the calculation of α-decay half-lives owing to its high sensitivity to the decay width.…”
Section: Introductionmentioning
confidence: 99%